2009
DOI: 10.1097/ncn.0b013e3181bcab43
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of a PDA-Based Home Hospice Care System for Cancer Patients

Abstract: This study describes a systematic and efficient point-of-care home hospice information system, which can effectively manage patient information and can easily be incorporated into a home hospice service using wired and/or wireless communications and mobile computing technology. To help with the design of a portable home hospice information system, we analyzed the services provided by visiting nurses and the opinions of users, based on the 2005 Guidelines for Cancer Patient Management Program of the Ministry of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 8 publications
0
11
0
1
Order By: Relevance
“… 9 As the telemedicine systems develop, home-based hospice is becoming more feasible and convenient. 10 , 11 Rural area previous in lack of hospice may benefit from home-based hospice care. 12 …”
Section: Introductionmentioning
confidence: 99%
“… 9 As the telemedicine systems develop, home-based hospice is becoming more feasible and convenient. 10 , 11 Rural area previous in lack of hospice may benefit from home-based hospice care. 12 …”
Section: Introductionmentioning
confidence: 99%
“…Using these devices for data collection has been shown to improve efficiency [5,23,30]. We argue here that using them provides an additional advantage: it can make it easier to detect curbstoning.…”
Section: Introductionmentioning
confidence: 94%
“…Consequently, these nurses indicated that accessing information using their mobile devices assisted them in their clinical practice [21] and improved the effectiveness and efficiency of patient care. [22] Other researchers have found that registered nurses who use mobile devices spent less time completing unnecessary paperwork [23] resulting in increased patient safety. [1,2,24,25]…”
Section: Mobile Technologiesmentioning
confidence: 99%